Sulh approach in the education loan’s repayment: The study on education loans of the National Higher Education Fund Corporation (PTPTN) / Dziauddin Sharif … [et al.] - Sharif, Dziauddin; Che Man, Norajila; Mohd Zain, Zainab; Pauzi, Nasif Sidquee; Ahmad Ubaidah, Ahmad Faiz (2017)
Sulh means reconciliation on a contract that when it is held, it seeks to achieve peace between two conflicting parties. Sulh has a great role in Islamic approach towards the creation of a peaceful society. In recognizing the role of Sulh to become an important means of finding a peaceful way, this paper discusses the concept of Sulh according to the perspective of the Qur'an and then adapts into the debt repayment‘s solution, especially on education loan. By concentrating a case study on PTPTN‘s repayment performance among borrowers, the sulh approach is thus applied to see the performance of borrowers in paying their debts. It is hoped that this approach stimulates lender and borrower to achieve an encouraging and intensifying reductions in loan-based performance.